中国成年人文化程度与体格指标的长期变化关系 - Tan, Y; Shen, Z; Yu, C; Guo, Y; Bian, Z; Pei, P; Du, H; Chen, J; Chen, Z; Lyu, J; Li, L (Zhonghua Yixuehui, Chinese Medical Association, 2019)
Objective: To evaluate the association of educational level with anthropometric measurements at different adult stages and their long-term changes in adults who participated in the second re-survey of China Kadoorie Biobank (CKB).